Is the critical velocity test a good tool for aerobic assessment of children swimmers? - Sousa, M.; Vilas-Boas, J. P.; Fernandes, R. J. (The Open Sports Sciences Journal, 2012)
Although swimmers are involved at very young ages in training and in competition, the differences in the physiological responses to exercise between them and adults are usually not respected. In fact, children swimmers are rarely involved in training control, leading to inadequate volume and prescription of training intensities. Our purpose was to verify if the critical velocity test is a good tool for aerobic assessment in children swimmers, by comparing it with the velocity corresponding to metabolic individual anaerobic threshold. Fourteen swimmers of 10.7 ± 0.73 years old voluntarily participated in the present study. Critical velocity was determined as the slope of the regression line between two competitive events (100 and 400 m freestyle), and the corresponding official times. In addition, each participant performed a 5 x 200 m front crawl intermittent incremental protocol for individual anaerobic threshold assessment, with 30 s intervals and 0.05m/s increments between steps; the velocity at 4 mmol/l of blood lactate concentrations ([La-]) was also determined by extrapolation of the [La-]/velocity curve. The mean values obtained were: 1.04 ± 0.07, 1.03 ± 0.05 and 1.08 ± 0.06 m/s for the critical velocity, velocity at anaerobic threshold and velocity at 4mmol/l (respectively), being the first two parameters similar but lower than the velocity at 4 mmol/l. These results confirm that the critical velocity test is of simple and practical implementation, using data from competition (or by implementing maximal tests in training context), allowing to assess in a non-invasive way the aerobic capacity of children swimmers.